2003
DOI: 10.1159/000069777
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin and C-Reactive Protein in Infective Endocarditis: Correlation with Etiology and Prognosis

Abstract: Background: The aim of this study was to investigate the diagnostic values of serum procalcitonin (PCT) and C-reactive protein (CRP) levels in infective endocarditis (IE) and to correlate them with the etiology of the disease and the prognosis of the patients. Methods: Fifty patients who were diagnosed as having IE based on Duke criteria (major and/or minor) were included in the study at the Istanbul University Cardiology Institute and Florence Nightingale Hospital. Forty patients with bacteremia (non-IE) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
45
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 27 publications
(33 reference statements)
5
45
4
Order By: Relevance
“…Some previous studies (16,(18)(19)(20)(21) have shown that PCT levels were higher in patients with gram-negative bacteremia than in those with gram-positive bacteremia, while the present study and another previous study (9) failed to show such an association. Two candidemia episodes showed positive results for PCT with high CRP levels in our study, as previously reported (9).…”
Section: Discussioncontrasting
confidence: 86%
“…Some previous studies (16,(18)(19)(20)(21) have shown that PCT levels were higher in patients with gram-negative bacteremia than in those with gram-positive bacteremia, while the present study and another previous study (9) failed to show such an association. Two candidemia episodes showed positive results for PCT with high CRP levels in our study, as previously reported (9).…”
Section: Discussioncontrasting
confidence: 86%
“…The procalcitonin level was found to be 0.19 ng/mL (range 0.10 to 1.22 ng/mL) in healthy subjects. 8 Lamas and Eykyn 7 suggested the addition of a high C-reactive protein level as a minor criterion for the diagnosis of IE. Several studies in different clinical settings have shown that procalcitonin may be a more accurate marker of systemic bacterial infection than C-reactive protein.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the availability of biomarkers is of major interest. Several studies have investigated the application and usefulness of important laboratory markers for IE diagnosis (5)(6)(7)(8)(9)(10)(11)(12). Other studies (13)(14)(15)(16) have focused on the clinical usefulness of serum Creactive protein (CRP), a marker most frequently used in Europe (13 ), in IE.…”
mentioning
confidence: 99%